The Psychological Effects of Covid-19 Pandemic on The Hotel Employees: A Case Study in Makassar, South Sulawesi, Indonesia - Zuardin, Zuardin; Azhar, Al; Putri, Setyaningtyas Karunia; Anggoro, Ari (International Conference on Sustainable Health Promotion, 2021)
This study sought to identify the anxiety level of the hotel employees in Makassar due to the Covid-19 pandemic, and then explored the factors that influence it. The structured questionnaire in the Google form containing demographic characteristics and the 7-item Generalized Anxiety Disorder scale (GAD-7) inquiry was distributed online to respondents. Univariate analysis, multivariate logistic regression analysis, and spearman’s correlation were used to analyse the 66 responses received. Results showed that 18.2%of respondents suffered severe anxiety, 7.6% moderate anxiety, and 28.8% mild anxiety. Unmarried hotel workers tended to be more anxious (OR = 3.12, 95% CI = 0.157 - 2.118) than those who already had a partner, people who lived in the red zone of the Covid-19 spread had greater anxiety levels (OR = 4.71, 95% CI = 0.545 - 2.554) compared to other areas. Daily-life difficulty and worried about social interaction had a positive correlation with anxiety level